(untitled) - Bisen, Prakash S. (New Jersey, 2012)
Microbes affect our lives in a variety of ways—playing an important role in our health, food, agriculture, and environment. While some microbes are beneficial, others are pathogenic or opportunistic.
Keywords: Microbiology,Microbial biotechnology,Công nghệ sinh học vi sinh vật,Vi trùng học